Local Herbs Used in Concoction for Herbal Rice Preparation by Kelantan Siamese Community in Malaysia - Karunakaran, T. (H. : ĐHQGHN, 2018)
Herbs play a critical role, mainly as food source and supplementary source of natural medicine. In Malaysia there are numerous communities and ethnic groups who are still performing the use of herb as a part of their daily cuisine. One such community in Malaysia is the Siamese community of Kelantan, located on northern part of Kelantan, adjoining to Thailand. This community has historic tradition of consuming herbs with medicinal value. They consume a large number of herbs as concoction in rice cooking, also known as „herbal rice‟. This study was piloted to survey and record the type and parts of herbs used in the concoction. The current study was conducted via in-depth interview with local people from three village in Kelantan namely Kampung Kuang, Tanah Merah, Kampung Pasir Puteh, Tumpat dan Kampung Mentua, Tumpat, Kelantan. Total 45 herbs belonged to 24 families were documented. The parts of herb being consumed and used in concoction were leaves, stem, stalk, flower and rhizome.